2012
DOI: 10.1186/1741-7015-10-30
|View full text |Cite
|
Sign up to set email alerts
|

The effects of multi-domain versus single-domain cognitive training in non-demented older people: a randomized controlled trial

Abstract: BackgroundWhether healthy older people can benefit from cognitive training (CogTr) remains controversial. This study explored the benefits of CogTr in community dwelling, healthy, older adults and compared the effects of single-domain with multi-domain CogTr interventions.MethodsA randomized, controlled, 3-month trial of CogTr with double-blind assessments at baseline and immediate, 6-month and 12-month follow-up after training completion was conducted. A total of 270 healthy Chinese older people, 65 to 75 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
154
3
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(172 citation statements)
references
References 43 publications
9
154
3
6
Order By: Relevance
“…Cognitive studies have shown that even in advanced age, the brain displays certain plasticity (Berry et al, 2010;Cheng et al, 2012;Edwards et al, 2002Edwards et al, , 2005Jones et al, 2006;Smith et al, 2009). Structural imaging has shown substantial age-related gray and white matter shrinkage, especially in anterior brain regions (lateral prefrontal cortex), the hippocampus, and basal ganglia while neural loss is minimal in the occipital brain areas (Raz et al, 2005).…”
Section: Theories Of Cognitive Aging-based On Neuroplasticitymentioning
confidence: 99%
See 3 more Smart Citations
“…Cognitive studies have shown that even in advanced age, the brain displays certain plasticity (Berry et al, 2010;Cheng et al, 2012;Edwards et al, 2002Edwards et al, , 2005Jones et al, 2006;Smith et al, 2009). Structural imaging has shown substantial age-related gray and white matter shrinkage, especially in anterior brain regions (lateral prefrontal cortex), the hippocampus, and basal ganglia while neural loss is minimal in the occipital brain areas (Raz et al, 2005).…”
Section: Theories Of Cognitive Aging-based On Neuroplasticitymentioning
confidence: 99%
“…Some clinical trials, however, have shown transfer to other domains different than that of the trained exercises (Cheng et al, 2012;Mahncke et al, 2006;Oswald et al, 2006;Richmond et al, 2011;Willis et al, 2006).…”
Section: Computerized Brain Training In Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally these findings suggest that the implementation of CT with aging adults with MCI is effective in improving various aspects of memory performance, executive functioning, processing speed, attention, fluid intelligence and subjects' perception of memory functioning, as measured by formal and task specific measures, as well as particular MRI measures of brain connectivity. In seven out of 26 randomized control trials where follow-up data was provided, positive effects on memory, recall, speed of processing and fluid intelligence were preserved anywhere from one week to two years following training [12][13][14].…”
Section: Introductionmentioning
confidence: 99%